Karakter Pendidikan untuk Membentuk Pendidikan Karakter - Jalil, Abdul (FITK UIN Walisongo, 2012)
Existence of madrasa over time increasingly eroded by the waves 'leveling' on behalf of accreditation. As an initiative to defend against scour vision of civiliza-tion, educational institution of Qudsiyyah finally returned to khittah to establish Ma'had Qudsiyyah in Kudus which concentrates on aspects of ulu>mul fiqh. Goals to be achieved is a man of character formation intact (al-Kaun al-jami>') and the balance between mind and heart, body and spirit, skill and character, as well as cognitive, affective and psychomotor. Ma'had Qudsiyyah have set up processes and educational management that reflects management measures, implementation strategies, readiness of human resources of education and edu-cation, indicators of success of the program, design a comprehensive program contains content and contextual analysis of the educational process, technical evaluation and monitoring programs and policy formulation.AbstrakEksistensi madrasah dari waktu ke waktu semakin tergerus oleh gelombang ‘penyamarataan’ atas nama akreditasi. Sebagai ikhtiar untuk mempertahankan visinya melawan gerusan peradaban, lembaga pendidikan Qudsiyyah akhirnya kembali ke khittah dengan mendirikan Ma’had Qudsiyyah Menara Kudus yang berkonsentrasi pada aspek ulu>mul fiqh. Tujuan yang hendak dicapai adalah terbentuknya manusia yang berkarakter utuh (al-kaun al-jami>’) dan seimbang antara akal dan hati, jasmani dan rohani, keterampilan dan akhlak, serta kognitif, afektif dan psikomotorik. Ma’had Qudsiyyah telah menyiapkan proses dan ma-najemen pendidikan yang mencerminkan langkah-langkah pengelolaan, strategi implementasi, kesiapan SDM pendidikan dan kependidikan, indikator-indikator keberhasilan program, desain program yang komprehensif berisikan muatan dan analisis kontekstual proses pendidikan, teknik evaluasi program dan pengawasan dan formulasi kebijakan.